2020
DOI: 10.5539/ijel.v10n5p162
|View full text |Cite
|
Sign up to set email alerts
|

A Research Investigation of Contextualized Grammar Instruction from the Perspective of English Language Lecturers and Students at Al-Imam Mohammad Ibn Saud Islamic University

Abstract: This study investigated implicit versus explicit EFL grammar instruction by surveying the beliefs of university lecturers and students at the College of Languages and Translation at Al-Imam Mohammad Ibn Saud Islamic University/KSA regarding this significant issue. Many university lecturers who responded to the questionnaire instrument in the present study supported contextualized (implicit) grammar instruction. Likewise, open-ended questionnaire responses provided by a number of university students, at the abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Recent research has emphasized the importance of implicit grammar teaching and its integration into teaching tools, as highlighted by Vold (2020). This approach has gained significant support from university professors, as indicated by Alkhawaldeh (2020), who found that a large percentage of professors prefer implicit grammar instruction. Several benefits of implicit grammar teaching have been identified, including improved application of grammar concepts, enhanced morale among students (Thorpe, 2021), and the ability to grasp essential meaning without external intervention (Giguashvili & Sanaia, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has emphasized the importance of implicit grammar teaching and its integration into teaching tools, as highlighted by Vold (2020). This approach has gained significant support from university professors, as indicated by Alkhawaldeh (2020), who found that a large percentage of professors prefer implicit grammar instruction. Several benefits of implicit grammar teaching have been identified, including improved application of grammar concepts, enhanced morale among students (Thorpe, 2021), and the ability to grasp essential meaning without external intervention (Giguashvili & Sanaia, 2021).…”
Section: Introductionmentioning
confidence: 99%